2003
DOI: 10.1002/jctb.935
|View full text |Cite
|
Sign up to set email alerts
|

Potassium hexacyanocobalt ferrate and ammonium molybdophosphate sorption bags for the removal of 137Cs from aqueous solutions and a simulated waste

Abstract: 137 Cs recovery from the used sorbents was ∼0.46 g g −1 using 6 N HCl as leachant for AMP, compared with ∼0.253 g g −1 for KCFC using 6 N NaCl. These results indicated stronger cesium immobilization in the KCFC complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Note that some Prussian blue analogs, like cobalt ferrocyanide [6,7] and copper ferrocyanide [8], are highly water-insoluble; can be used directly as adsorbents for radioactive cesium eliminations. However, these analogs are costly compared to Prussian blue.…”
Section: Introductionmentioning
confidence: 99%
“…Note that some Prussian blue analogs, like cobalt ferrocyanide [6,7] and copper ferrocyanide [8], are highly water-insoluble; can be used directly as adsorbents for radioactive cesium eliminations. However, these analogs are costly compared to Prussian blue.…”
Section: Introductionmentioning
confidence: 99%
“…Thus innovative immobilization without losing value is highly desired for the present applications11. Note that some PB analogs, like cobalt ferrocyanide1516 and copper ferrocyanide12, are highly water-insoluble; these analog could be used directly as adsorbents for radioactive cesium eliminations. However, these analogs are costly compared to PB.…”
mentioning
confidence: 99%
“…8 The success of the ORNL work led to development efforts aimed at Cs treatment of SRS HLW. 9 As for tea bags, a journal article 10 published near the end of the current study showed that others have considered the bag concept for treatment of fission products.…”
Section: Previous Workmentioning
confidence: 88%